Achieving Green Competitive Advantage Through Organizational Green Culture, Business Analytics and Collaborative Competence: The Mediating Effect of Eco-Innovation - Widiyati, Dian; Murwaningsari, Etty (IJOSMAS, 2021)
This research determines to inspect the contribution of the eco-innovation (EI) in transforming the organizational green culture (OGC), business analytics (BA) and collaborative competence (CC) to enhance of green competitive advantage (GCA). Structural equation model was developed to illustrate connection between organizational green culture, business analytics, collaborative competence, eco-innovation and GCA by escorting a survey of 169 Indonesian state-owned company managers. These results reveals that OGC has a sig. positive effect on EI, business analytics does not have a sig. positive clout on EI, CC has a significant positive clout on EI, organizational green culture has a positive clout on GCA, business analytics has no positive clout on GCA, CC has no positive clout on GCA and EI has a sig. positive clout on GCA, while EI as a partial mediator between organizational green culture and GCA, eco-innovation is not a mediating variable between business analytics and GCA and EI as a full mediator between collaborative competence and GCA. This research expands the debate by examining eco-innovation and business analytics in obtaining GCA of how companies can spring up with the well-being system.